1992
DOI: 10.1108/08876049210035872
|View full text |Cite
|
Sign up to set email alerts
|

Service Provider Job Satisfaction and Customer

Abstract: Considers the impact of multi‐faceted measures of job satisfaction on customer‐oriented behaviours demonstrated by service providers. Reveals how overall job satisfaction, together with specific satisfaction related to supervision, colleagues, promotion and work are positively related to customer‐orientation, while satisfaction with pay is not of significance in this case. Discusses recommendations for management and suggestions for further research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
148
2
4

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 238 publications
(159 citation statements)
references
References 0 publications
5
148
2
4
Order By: Relevance
“…In 3 latent variables (working environment, employee living conditions, and working rewards) that constituted employee satisfaction, only the effect of working rewards on service quality is not significant, the rest of the variables are positively affecting the service quality. It is consistent with the research conclusions of Douglas in 1992 that "with high employee satisfaction, employees would be more prone to service-oriented behavior, thus providing high quality service in the process of service delivery" [33]. And at the same time, high employee satisfaction also positively affects the service quality through employee emotion.…”
Section: Resultssupporting
confidence: 79%
“…In 3 latent variables (working environment, employee living conditions, and working rewards) that constituted employee satisfaction, only the effect of working rewards on service quality is not significant, the rest of the variables are positively affecting the service quality. It is consistent with the research conclusions of Douglas in 1992 that "with high employee satisfaction, employees would be more prone to service-oriented behavior, thus providing high quality service in the process of service delivery" [33]. And at the same time, high employee satisfaction also positively affects the service quality through employee emotion.…”
Section: Resultssupporting
confidence: 79%
“…Previous empirical studies evidently presents strong relationship between employee performance and customer satisfaction. Study of Douglas, Thomas, &Ingram, (1992) andFrederick Reichheld (2000), presents a positive correlation with customer oriented behavior and concluded that employee performance is essential to customer satisfaction. Likewise, Heskett, Jones, Loveman, Sasser, and Schlesinger (1994) establish a framework in which internal service quality drives employee satisfaction, which, in turn, drives employee performance that generates service quality.…”
Section: Employees' Perceived Job Performance and Customer Satisfmentioning
confidence: 99%
“…Much of the burden for customer perceptions of service quality lies on front-line personnel (Hoffman and Ingram, 1992). The consequences of customer satisfaction is linked with employee performance in several studies.…”
Section: Employees' Perceived Job Performance and Customer Satisfmentioning
confidence: 99%
“…Edward and Scullion (1982) identified the meaning of job satisfaction as the overall measurement of working attitudes of the reception, happiness, and pleasure in the job. Employees' job satisfaction is also concerned with supervision quality, working conditions, intrinsic compensation, benefits, and company policies (Hoffman & Ingram, 1992). Robbins and Coulter (1996) stated that job satisfaction is an employee's general attitude towards his or her job.…”
Section: Job Satisfactionmentioning
confidence: 99%